Phylotranscriptomics Resolves the Phylogeny of Pooideae and Uncovers Factors for Their Adaptive Evolution. (3rd February 2022) - Zhang, Lin; Zhu, Xinxin; Zhao, Yiyong; Guo, Jing; Zhang, Taikui; Huang, Weichen; Huang, Jie; Hu, Yi; Huang, Chien-Hsun; Ma, Hong
Abstract: Adaptation to cool climates has occurred several times in different angiosperm groups. Among them, Pooideae, the largest grass subfamily with ∼3, 900 species including wheat and barley, have successfully occupied many temperate regions and play a prominent role in temperate ecosystems. To investigate possible factors contributing to Pooideae adaptive evolution to cooling climates, we performed phylogenetic reconstruction using five gene sets (with 1, 234 nuclear genes and their subsets) from 157 transcriptomes/genomes representing all 15 tribes and 24 of 26 subtribes. Our phylogeny supports the monophyly of all tribes (except Diarrheneae) and all subtribes with at least two species, with strongly supported resolution of their relationships. Molecular dating suggests that Pooideae originated in the late Cretaceous, with subsequent divergences under cooling conditions first among many tribes from the early middle to late Eocene and again among genera in the middle Miocene and later periods. We identified a cluster of gene duplications (CGD5) shared by the core Pooideae (with 80% Pooideae species) near the Eocene–Oligocene transition, coinciding with the transition from closed to open habitat and an upshift of diversification rate. Molecular evolutionary analyses homologs of CBF for cold resistance uncovered tandem duplications during the core Pooideae history, dramatically increasing their copy number and possibly promoting adaptation to cold habitats. Moreover, duplication of AP1 / FUL -like genes before the Pooideae origin might have facilitated the regulation of the vernalization pathway under cold environments. These and other results provide new insights into factors that likely have contributed to the successful adaptation of Pooideae members to temperate regions.